Surface Deformation Monitoring from SAR Interferometry for Seismic Hazard Assessment Around Major Active Faults: Case of Zemmouri Earthquake (Algeria) - Aguemoune, S. (2022)
In seismogenic zones, geodetic campaigns are usually used to monitor the ground deformation. Nowadays, satellite imaging became a powerful tool to monitor surface deformation on very large areas using InSAR (Interferometry Synthetic Aperture Radar). To get reliable results, reducing errors became a real challenge. We recently proposed a new phase unwrapping procedure and a new technique to reduce atmospheric errors. These techniques were assembled to develop a new InSAR time series methods named ISBAS (Improved Small BAseline Subsets). We tested our procedure on Zemmouri (Algeria) seismogenic zone struck by an Mw 6.8 earthquake in 2003. Several SAR images from ENVISAT satellite were used in combination with data from MERIS tool embed- ded on the same satellite to monitor post-seismic deformation. Our analysis highlights the zones of signif- icant deformation due to not only post-seismic seismic movement, but also to other anthropogenic origin. This kind of studies can really help to better assess the seismic hazard around major active fault such as that of Zemmouri and on other active sources that could generates strong seismic events.